Incidental chest computed tomography findings in asymptomatic Covid-19 patients. A multicentre Indian perspective - Ramanan, Rochita V; Joshi, Anagha R; Venkataramanan, Akash; Nambi, Senthur P; Badhe, Rashmi (Indian Journal of Radiology and Imaging, 2021)
In December 2019, an unprecedented outbreak of pneumonia of unknown etiology emerged called COVID-19. A vast number of people affected by this disease are asymptomatic and yet contagious with up to 79% of COVID-19 infections reportedly caused by undocumented infections. Surprisingly, these asymptomatic subjects are also known to quietly harbor pneumonia changes on CT scans. RT-PCR, the definitive test for COVID-19, maybe false negative in patients with COVID-19 pneumonia on CT. Incidental findings highly suspicious of COVID-19 pneumonia on CT chest of asymptomatic patients may increase as the community transmission of the virus rises and isolation restrictions are released. It is advisable to be aware of its appearances and the challenges associated with it.
Keywords: Asymptomatic COVID-19 patients; false positive RT-PCR; incidental COVID-19 pneumonia on CT; RT-PCR COVID-19